GENIUS LEARNING STRATEGY BERBASIS MAGIC FORMULASEBAGAI UPAYA PENINGKATAN HASIL BELAJAR SISWAKELAS V MAPEL MATEMATIKA MATERI BANGUN RUANGDI SD NEGERI KOWANGBINANGUN KALASAN - Arman Riyadi, Agustriyaningsih Setiadi, Andarini Permata C. (Pelita - Jurnal Penelitian Mahasiswa UNY, 2009)
This study is intended to know about the role of Magic Formula-Based GeniusLearning Strategy can improve the output of mathematic learning at SD NegeriKowangbinangun Kalasan.The study employed a quasi-experimental approach. The technique of datacollection was done by participation observation and documentation. The subject of theresearch was the students Grade V at SD Negeri Kowangbinangun, Kalasan.The result of the study shows that the implementation of Magic Formula-BasedGenius Learning Strategy achieved good results, meaning that the students had activerole in the learning process. This strategy could increase and motivate the students tolearn mathematics, specifically geometry or shape. The postest of the second cycleproduced better scores. The students’ average scores was 5. 25 and the average scoresin the posttest of the second cycle was 8.15. The student also became active and thesituation of mathematic class became enjoyable.Keywords : Magic Formula-based Genius Learning Strategy, output of mathematic learning,geometry